Production of in vivo biotinylated scFv specific to almond (Prunus dulcis) proteins by recombinant Pichia pastoris - de la Cruz, Silvia; Alcocer, Marcos; Madrid, Raquel; García, Aina; Martín, Rosario; González, Isabel; García, Teresa (Elsevier, 2016)
The methylotropic yeast Pichia pastoris has demonstrated its suitability for large-scale production of recombinant proteins. As an eukaryotic organism P. pastoris presents a series of advantages at expression and processing of heterologous proteins when compared with Escherichia coli. In this work, P. pastoris has been used to express a scFv from a human synthetic library previously shown to bind almond proteins. In order to facilitate purification and post processing manipulations, the scFv was engineered with a C-terminal tag and biotinylated in vivo. After purification, biotinylated scFv were bound to avidin conjugated with HRP producing a multimeric scFv. The multimeric scFv showed to maintain their ability to recognize almond protein when assayed in ELISA, reaching a LOD of 470 mg kg−1. This study describes an easy method to produce large quantities of in vivo biotinylated scFv in P. pastoris. By substituting the enzyme or fluorochromes linked to avidin, it will be possible to generate a diverse number of multimeric scFv as probes to suit different analytical platforms in the detection of almond in food products.